2021
DOI: 10.1107/s160057752100477x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of strain on image reconstruction in Bragg coherent X-ray diffraction imaging and ptychography

Abstract: A quantitative analysis of the effect of strain on phase retrieval in Bragg coherent X-ray diffraction imaging is reported. It is shown in reconstruction simulations that the phase maps of objects with strong step-like phase changes are more precisely retrieved than the corresponding modulus values. The simulations suggest that the reconstruction precision for both phase and modulus can be improved by employing a modulus homogenization (MH) constraint. This approach was tested on experimental data from a highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Previous BCDI studies have shown that the strain changes due to gas adsorption are localized at specific corners, edges, and facets, with density functional theory (DFT) studies showing the energies of adsorption differ for {111} and {110} facets. 12,15 For the shown nanoparticle, changes in strain are close to the top {111} facet during the CO condition, and across all facets during the reaction. Examples of the reconstructed particle strain are shown for each gas condition (dynamic and steady-state) in Figure 2c.…”
Section: Co Oxidation Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous BCDI studies have shown that the strain changes due to gas adsorption are localized at specific corners, edges, and facets, with density functional theory (DFT) studies showing the energies of adsorption differ for {111} and {110} facets. 12,15 For the shown nanoparticle, changes in strain are close to the top {111} facet during the CO condition, and across all facets during the reaction. Examples of the reconstructed particle strain are shown for each gas condition (dynamic and steady-state) in Figure 2c.…”
Section: Co Oxidation Reactionmentioning
confidence: 99%
“…In order to probe the catalytically driven reaction, previous works have focused on the evolution of catalyst strain in well-faceted NPs. In addition to facet-dependent catalytic activity, lattice strain is known to influence the reactivity of metal surfaces. A metal of particular interest, Pt, exhibits an increase (decrease) in the 5d-band energy by as much as 0.1 eV under a 1% tensile (compressive) strain .…”
Section: Introductionmentioning
confidence: 99%